Rectal Douching and Microbicide Acceptability among Young Men who Have Sex with Men - Tingler, Ryan C (AIDS Behav, 2020)
Men who have sex with men (MSM) commonly report engaging in rectal douching (RD) practices prior to receptive anal intercourse. Researchers are interested in the possibility of designing a RD with a microbicide component. In our analyses, we examined whether YMSM who engaged in RD behaviors differ in HIV prevention behaviors from their non-RD peers. We then examined whether RD frequency was associated with rectal microbicide acceptability. Half the participants (47.8%) reported having ever douched. Participants were more likely to douche if they were racial/ethnic minorities (AOR=2.24, p=.02) and had recently tested for HIV (AOR=1.96, p=.04). Greater douching frequency was associated with racial/ethnic minorities (β=.20, p=.009) and recent HIV testing (β=.19, p<.01). Participants who reported frequently douching indicated greater microbicide acceptability (β=.32, p<.001). Designing behaviorally congruent products remains a priority in next generation Pre-Exposure Prophylaxis (PrEP) and a rectal douche might be an additional tool if found to be efficacious.